Жанротвірні координати постмодерністського пастишу - Бербенець, Л. (Літературознавчі обрії. Праці молодих учених, 2010)
In postmodernism genre cannons seem to be entirely rejected. But they still allow comparing postmodernist eclectic and non-conventional texts with the traditional genre forms and to state the non-genre nature of the former. Pastiche in postmodern literature tends to be aside from all the genre forms. But at the same time it possesses serious genrechanging potential being a kind of metagenre construction.